The Relevance of The Madrasah Aliyah Fiqh Package Book Published By The Indonesian Ministry of Religion With The 2013 Curriculum - Mhd. Reza Fahlevi; Asnil Aidah Ritonga; Wahyuddin Nur Nasution (Nazhruna: Jurnal Pendidikan Islam, 2021)
This study aims to describe and analyze fiqh textbooks for madrasah aliyah subjects in Batubara Regency. This study uses a qualitative approach with the R&D method. The results of this study indicate that (1) the madrasah aliyah fiqh package book published by the Ministry of Religion of the Republic of Indonesia in Batubara Regency is relevant to the KD component (basic competence) of the 2013 curriculum and is student-centered (student-centered learning); (2) the book component is considered feasible based on the feasibility test which obtains an average score of 67.01 (good category); (3) language suitability is also assessed as accurate and precise, and in accordance with the level of intellectual development of students at the madrasah aliyah level, based on the feasibility test, obtaining an average score of 70.83 (good category); and (4) the presentation of the book is considered good with an average test score of 84.37 (good category) and meets the aspects of graphic standardization in the content design, book size, and cover section. Overall, it was concluded that the madrasah aliyah fiqh textbooks in Batubara Regency were worthy and in a good category to be distributed as reading material for madrasah aliyah students.